Sedimentological and geochemical compositions of the Lake Petit sediments (Southern French Alps) - Elodie Brisset (PANGAEA, 2020)
A 144-cm long sediment core named PET09P2 (coordinates N 44°06.789; E 7°11.342) has been taken in 2009 in the Lake Petit (2200 m a.s.l., in the Southern Alps, city of Valdeblore, France), covering the Mid- to Late-Holocene period (last 4800 years BP). This dataset includes the sedimentological and geochemical analyses, that were used as proxies to reconstruct catchment and lake paleoenvironmental changes: - Age-depth model based on radiocarbon ages (7 samples) and short-lived isotopes (210Pb, 137Cs). - Clay-size particles abundance (Grain-size laser diffraction measured on a Malvern Mastersizer S at 5 mm sampling intervals). - Total organic carbon concentrations in per cent (24 discrete samples by Rock-Eval Pyrolysis on a Turbo Model RE6 pyrolyser), as well as Hydrogen and Oxygen Indexes (mg/g of total organic carbon). - Major element concentrations in per cent (SiO2, Al2O3, Fe2O3, MnO, MgO, CaO, Na2O, K2O, TiO2, P2O5 measured by mass spectrometry on an ICP-AES Thermo X7 after LiBO2 alkaline fusion) and, biogenic silica (SiO2biog) concentration in per cent measured after wet-alkaline leaching using molybdate-yellow spectrophotometry on a Jasco V-650 Spectrophotometer. - Fourier Transformed Infrared Spectroscopy (FTIRS) inference for SiO2 biogenic and TOC concentrations in per cent (continuous sampling at 1 cm intervals), measured on a Nicolet 380 Smart Diffuse Reflectance spectrometer. - XRF core scanning inference for Detrital Fraction (DF% = 6.2*Ln[Ti/Si]+20.8), and Chemical Index of Alteration (Ln[Ti/Ca]); measure on an ITRAX Core Scanner (Mo source, 2 mm increment, integration time 60 s, energy 40 kV-35 mA). As shown in Brisset et al., (2013), the relationship between the Ln(Ti/Ca) XRF intensities and the CIA (%) is linear and positive, and both are highly related (n = 20, r = 0.90).